2016
DOI: 10.1002/wnan.1412
|View full text |Cite
|
Sign up to set email alerts
|

Detection and treatment of atherosclerosis using nanoparticles

Abstract: Atherosclerosis is the key pathogenesis of cardiovascular disease, which is a silent killer and a leading cause of death in the United States. Atherosclerosis starts with the adhesion of inflammatory monocytes on the activated endothelial cells in response to inflammatory stimuli. These monocytes can further migrate into the intimal layer of the blood vessel where they are differentiate into macrophages, which take up oxidized low-density lipoproteins and release inflammatory factors to amplify the local infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 193 publications
(439 reference statements)
2
80
0
1
Order By: Relevance
“…Moreover, no obvious difference in the organ index of heart, liver, spleen, lung, and kidney was observed, suggesting no significant toxicity to the main organs ( Figure 8B). 2019, 6,1900172 indicated that the functions of the liver and kidney were not impaired by the treatment (Figure 8C-F). In addition, the blood biochemical assays of alanine aminotransferase (ALT), aspartate aminotransferase (AST), creatinine (CREA), and blood urea nitrogen (UREA) were at normal levels, which Adv.…”
Section: Biosafety Assessmentmentioning
confidence: 92%
See 2 more Smart Citations
“…Moreover, no obvious difference in the organ index of heart, liver, spleen, lung, and kidney was observed, suggesting no significant toxicity to the main organs ( Figure 8B). 2019, 6,1900172 indicated that the functions of the liver and kidney were not impaired by the treatment (Figure 8C-F). In addition, the blood biochemical assays of alanine aminotransferase (ALT), aspartate aminotransferase (AST), creatinine (CREA), and blood urea nitrogen (UREA) were at normal levels, which Adv.…”
Section: Biosafety Assessmentmentioning
confidence: 92%
“…However, when compared with DiD@PLGA, phagocytosis of RBC/DiD@PLGA by macrophages was noticeably reduced. 2019, 6,1900172 phagocytosis. However, the internalization signal of RBC/DiD@PLGA was significantly lower than that of DiD@PLGA, as evidenced by 1.6-, 2.6-, 3.3-, and 2.9-fold decreases at 1, 2, 4, and 8 h incubation, respectively ( Figure 3F).…”
Section: Rbc/rap@plga Nanoparticles Display Immune-evasive Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, lots of literatures report the possibility of multimodality molecular imaging using nanoprobes, which supports the notion that clinical translation of this technology will be feasible in the near future [7,9,10]. Hence, the purpose of this review is to provide readers with a current update of multimodality molecular imaging of cardiovascular disease based on nanoprobes, which focus on six important aspects of cardiovascular diseases, including atherosclerosis, thrombosis, myocardial infarction and postinfarction remodeling, angiogenesis, apoptosis and cardiac stem cell-based therapy.…”
Section: Introductionmentioning
confidence: 62%
“…As more polymer nanomicelles have been recently proposed for atherosclerosis detection and treatment via targeting the intimal macrophages, foam cells and endothelial cells [20], one would expect that internalization of PMs into atherosclerotic plaques could possibly alter either plaque architecture or composition, thereby increase or decrease in PSS. However increased PSS levels may be a principal mechanism through which plaques rupture, resulting in thrombosis and sudden ischemic clinical events.…”
Section: Biomechanical Forces a Distinct Perspective?mentioning
confidence: 99%